Photodegradation studies on C. I. reactive red 158 - Miranda, Teresa (2006)
Dye-containing wastewater generated from textile industries is a major source of environmental pollution. Azo dyes, which are the largest group of coloring agents, are widely used in industry. Advanced Oxidative Processes are very promising for effluent treatment mainly due to their high efficiency and simplicity of operation. Our group became interested on photocatalytic methods (included in the AOP’s), using TiO2, for degradation of dyes, started with simpler structures and continued with commercial dyes. Titanium dioxide (TiO2) has proven to be the most effective and suitable catalyst for photocatalytic reaction due to its low cost economical, chemical stability, and insolubility. In this paper, the effects of UV light irradiation in the presence of TiO2 particles at various pH’s (3, 6, 8 and 10) on the photodegradation of an azo dye, Reactive Red 158, were investigated. The photocatalytic degradation was carried out either in aqueous solutions or in a synthetically prepared dyebath effluent, under UV irradiation, in the presence of Degussa P25 TiO2 as the catalyst. Reactive dyes of the pyrimidinyl type partly hydrolyse during dyeing in basic medium; RR 158 was hydrolysed and this solution was also irradiated. The fastest degradation was obtained with an acid solution (14 minutes, 95.53% loss of colour), but the hydrolysed dye took longer to be decolourised.